2019
DOI: 10.2196/13674
|View full text |Cite
|
Sign up to set email alerts
|

Development and Efficacy of an Electronic, Culturally Adapted Lifestyle Counseling Tool for Improving Diabetes-Related Dietary Knowledge: Randomized Controlled Trial Among Ethnic Minority Adults With Type 2 Diabetes Mellitus

Abstract: BackgroundEthnic minority populations exhibit disproportionately high rates of type 2 diabetes mellitus (T2DM). Electronic health tools have the potential to facilitate the cultural adaptation and tailoring of T2DM education to improve the knowledge and management of diabetes mellitus (DM).ObjectiveThis study aimed (1) to develop an adaptable Interactive Lifestyle Assessment, Counseling, and Education (I-ACE) software to support dietitian-delivered lifestyle counseling among low-socioeconomic status (SES) ethn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Four mixed methods studies were rated ranging from 66% (10/15 items) to over 80% (13/15 items) [ 18 , 32 34 ]. The rest of the articles were rated 60% (3/5 items, n = 10) [ 20 , 35 43 ] or 80% (4/5 items, n = 12) [ 21 , 44 54 ]. The MMAT scores are presented in Table 2 and Additional file 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four mixed methods studies were rated ranging from 66% (10/15 items) to over 80% (13/15 items) [ 18 , 32 34 ]. The rest of the articles were rated 60% (3/5 items, n = 10) [ 20 , 35 43 ] or 80% (4/5 items, n = 12) [ 21 , 44 54 ]. The MMAT scores are presented in Table 2 and Additional file 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Patients’ usability of eHealth was effective or positive in most articles (61.54%, n = 8/13) [ 34 , 35 , 38 , 39 , 44 , 46 , 52 , 54 ]. Four articles (30.77%) showed both satisfaction (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][34][35][36][37][38][39] Numerous studies have explored PA as a stand-alone topic for counselling, 17,[19][20][21]34,37,[39][40][41][42] while others have explored counselling for combinations of PA and other health behaviors (eg nutrition, smoking, and alcohol use). 15,16,18,23,35,36,38,[43][44][45][46][47][48][49][50][51] Among these studies, the outcomes of using eHealth technologies for PA counselling in PHC settings were diverse. 52 This is reflective of the different needs across the wide range of PHC settings.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…mHealth technology has increasingly been integrated into health care to meet the demands of diabetic care during the COVID-19 pandemic. It has been shown to be effective at enhancing health outcomes, such as medication adherence, glycated hemoglobin (HbA 1c ) levels, and self-management [10][11][12][13][14][15][16][17][18]. Studies have shown that multimedia education using videos is more effective than written information in terms of engagement and information uptake [19,20].…”
Section: Introductionmentioning
confidence: 99%